Anti-inflammatory effects of trihoney in hypercholesterolemic atherosclerotic rabbits: a comparative study with atorvastatin - Hamad Alfarisi, Hamad Abdulsalam; Ibrahim, Muhammad; Azahari, Nuraniza; Hamad Mohamed, Zenab; Hamdan, Asmah Hanim; Che Mohamad, Che Anuar (Universiti Putra Malaysia, 2020)
Introduction: Hypercholesterolemia has been proven as a main pathogenic trigger for pathogenesis of atherosclero- sis. Atherosclerosis characterised by chronic inflammatory process and increased expression of inflammatory mark- ers. In this study; Trihoney (a combination of three types of natural honey namely: Trigona, mellifera, and Dorsata) was investigated for its anti-inflammatory effect in hypercholesterolemic atherosclerotic rabbits. Methods: Thirty male New Zealand white rabbits (NZW) were grouped into: normal diet (C), normal diet with 0.6g/kg/day of Tri- honey (C+H), 1% cholesterol diet (HCD), 1% cholesterol diet with 0.6g/kg/day of Trihoney (HCD+H), and 1% cholesterol diet with 2mg/kg/day of atorvastatin (HCD+At.). After 12 weeks of starting the experiment, animals were sacrificed and serum analysed for homocysteine and pro-atherogenic inflammatory markers such as: interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumour necrosis factor-α (TNF-α). Fasting serum glucose was analysed to assess gly- caemic status. Results: Trihoney treated group showed significantly lower (p<0.05) serum IL-1β and IL-6 compared to the HCD group. Trihoney supplementation resulted in significant (p<0.001) reduction of serum TNF-α compared to HCD group. Experimental group HCD had serum homocysteine level comparable to that of the control groups with- out any significant difference despite little increase in the mean value. Trihoney treated group had serum homocys- teine comparable to the controls. All experimental groups showed fasting serum glucose comparable to the control. Conclusion: This study showed that Trihoney has an anti-inflammatory function and may be used as an adjuvant to statins for management of atherosclerotic cardiovascular diseases even in diabetic subjects. Keywords: Atherosclerosis, Atorvastatin, Inflammatory markers, Trihoney